Antioxidant and Antibacterial Activities of the Methanolic Extract from Sphagneticola trilobata - Queen, Paulraj Darthi; Pavithra, Krishnasamy; Ragunath, Cholaraj; Karthik, Madeshwaran; Ramasubramanian, Venkatachalam (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
The objective of this study is to assess the phytochemical activity of the methanolic extract of Sphagneticolatrilobata (L.) and to evaluate the bioactive compounds present using gas chromatography-mass spectrometry (GC-MS). The objective of this study is to investigate the potential anticancer, antibacterial, and antioxidant properties of the methanolic extract derived from S. trilobata. The bioactive compounds of S. trilobata were identified through the use of Gas Chromatography-Mass Spectrometry (GC-MS). The antioxidant properties of S. trilobata were assessed through DPPH (1,1-diphenyl-2-picrylhydrazyl),ABTS (2,2'-azino-bis-3-ethylbenzthiazoline-6-sulphonic acid), H2O2 (Hydrogen peroxide) and Superoxide dismutase (SOD) activity. The antibacterial properties of S. trilobata extract against Pseudomonas aeruginosa and Staphylococcus aureus were assessed using the disc diffusion technique, Minimum inhibitory concentrations, and growth curve analysis. The methanolic S. trilobata plant was contain 40 bioactive compounds. Among them amounts of oleic acid (100%), abietic acid (98.25%), and n-hexadecanoic acid (94.45%). The antioxidants revealed that dose dependent activity, the highest antioxidant activity was DPPH (53.5%), ABTS (54.7%), H2O2 (54.1%) and SOD (43.2%) at 1.5mg/mL. The antibacterial activity revealed that high antibacterial properties against P.aeruginosaand S. aureus inhibition zones of P. aeruginosa (14 ±0.8 mm) and S. aureus, both (12± 0.4 mm).The preliminary examination of the volatile compounds indicates the existence of novel bioactive constituents that have not been previously documented in S. trilobata from different geographic regions. The present study investigates the biological activities of the methanolic extract derived from S. trilobata leaves, with a focus on its potential applications in the pharmaceutical and nutraceutical fields.